Boosting CO2 hydrogenation to methane over Ni-based ETS-10 zeolite catalyst - Xiang, Mei; Gao, Zhangxi; Ji, Xiaonan; Li, Dantong; Deng, Yaoyao; Ding, Yalong; Yu, Chi; Zhang, Wei; Zhang, Zhenwei; Wu, Zeying; Zhou, Jiancheng (Frontiers in Chemistry, 2022)
The activation and conversion of the CO2 molecule have always been the most vexing challenge due to its chemical inertness. Developing highly active catalysts, which could overcome dynamic limitations, has emerged as a provable and effective method to promote CO2 activation–conversion. Herein, ETS-10 zeolite–based catalysts, with active nickel species introduced by in situ doping and impregnation, have been employed for CO2 methanation. Conspicuous CO2 conversion (39.7%) and perfect CH4 selectivity (100%) were achieved over the Ni-doped ETS-10 zeolite catalyst at 280°C. Comprehensive analysis, which include X-ray diffraction, N2 adsorption–desorption, SEM, TEM, H2 chemisorption, CO2 temperature programmed desorption, and X-ray photoelectron spectroscopy, was performed. Also, the results indicated that the resultant hierarchical structure, high metal dispersion, and excellent CO2 adsorption–activation capacity of the Ni-doped ETS-10 zeolite catalyst played a dominant role in promoting CO2 conversion and product selectivity.